Styx and scones in the sticky wand - Cooper, Jay, 1974- (Ready-to-read graphics. Superstar reader!, 2023)
"Styx and Scones are a cat and a dog who live with two friendly witches. When the witches leave, Scones finds what looks like a stick and wants to play with it. Styx wants to play too. Soon, magic is everywhere!"--Page 2 of cover